Us Experience In Training Water Management Personnel In Uzbekistan (Texas Journal of Multidisciplinary Studies, 2025)
This article provides US experience in training water management personnel in Uzbekistan, Besides, in the article has been analyzed the structure, main directions, and developmental stages of the training system for irrigation and reclamation specialists in the USA, established as a continuous and sustainable model meeting contemporary demands. The research encompasses the experience of the American educational system, highlighting the significance of integrating vocational training, higher education, and research institutions